Simulasi Rangka Gudang Terhadap Pembebanan Hoist Crane Double Grider 2 Ton Divisi GSCM PT. Xx: Warehouse Frame Simulation Against Double Grider 2 Ton Hoist Crane Loading GSCM Division PT. Xx - Muhammad Edgar Gazanata; Rudiat; Rifky Irfani (Jurnal Pendidikan Teknik Mesin Undiksha, 2025)
This study aims to analyze the permissible deflection limits of the warehouse frame structure in the GSCM Division of PT. Xx The analysis was carried out using Autodesk Inventor Professional 2024 to simulate the effect of a 2-ton double girder lifting crane load on a steel structure made of ASTM A36 material. Observations, measurements, literature studies, and interviews were conducted to collect the necessary data. The simulation results showed that the maximum deflection of the building structure was 1.71 mm, exceeding the permissible deflection of 0.599 mm according to SNI 1729:2015. Likewise, the maximum deflection of the lifting crane girder reached 65.68 mm, exceeding the permissible limit of 36.78 mm. These findings indicate that the warehouse frame structure in its current condition does not meet the safety standards for the installation of hoist cranes. The deflection that occurs risks reducing structural stability and causing operational failure. Therefore, additional reinforcement and modification of the frame design are needed to be able to support the crane load optimally and safely. The results of this study are expected to be a reference in developing industrial warehouse structure designs that are more efficient and in accordance with safety standards.